1985
DOI: 10.1128/jb.162.3.1250-1254.1985
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of dipicolinic acid in dormant spores of Bacillus subtilis by immunoelectron microscopy with colloidal gold particles

Abstract: The localization of dipicolinic acid in dormant spores of Bacillus subtilis was examined by an immunoelectron microscopy method with colloidal gold-immunoglobulin G complex. The colloidal gold particles were distributed mainly in the core regions of dormant spores and were not observed in those of germinated or autoclaved spores. This result clearly demonstrates that dipicolinic acid is localized in the cores of dormant spores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…After the SDS-PAGE, the proteins were transblotted to nitrocellulose and treated in the same way as described above. Separation of IgG from the antisera was carried out as described before (15). SDS inhibitor (Mr= 20,100).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the SDS-PAGE, the proteins were transblotted to nitrocellulose and treated in the same way as described above. Separation of IgG from the antisera was carried out as described before (15). SDS inhibitor (Mr= 20,100).…”
Section: Methodsmentioning
confidence: 99%
“…Electron microscopy and labeling with colloidal gold. For immunocytochemical staining, intact dormant spores and spore coat fractions were fixed in 8 % paraformaldehyde, embedded in glycol methacrylate (GMA)-Quetol 523-methyl methacrylate followed by polymerization by UV irradiation and cut as described before (15). For preparation of a section by usual fixation of dormant spores and purity of the vegetative cell membrane and spore coat preparations used, samples were fixed by the method of Ryter et al (23) and embedded in Quetol 653 according to the method of Kushida (16).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, Walker and Beesley reported on the application of protein A-gold technique for immunochemical staining of bacterial surface antigen (18). Kozuka et al also showed clearly the localization of dipicolinic acid in the core of the dormant spores by IgG (antirabbit IgG)-colloidal gold complex (7). Based on the results obtained from these preliminary experiments, conditions for avoiding the loss of antigenicity during fixation and embedding seemed to be mainly dependent on the property of samples, i.e., cell type, stage of cells, antigen, antibody, and so on.…”
Section: Bacillus Megaterium Atccmentioning
confidence: 99%
“…Dipicolinic acid (pyridine-2,6-dicarboxylic acid; DPA) is a unique component present in a large quantity (5-15%) in bacterial spores [1] and appears to be involved in spore stability [2], germination [2], and heat resistance [1,[3][4][5]. DPA is primarily located in the spore core [6,7] and has been proposed to be tightly packed with the vital cell constituents [8], linked with proteins [1,9] or amino acids [10], or intercalated with DNA [3]. Evidence from ultraviolet absorption spectra [11], "Correspondence to: Y. Matano, Department of Microbiology, Nagoya City University Medical School, Mizuho-ku, Nagoya 467, Japan.…”
Section: Introductionmentioning
confidence: 99%